Negative Politeness Strategies in Collen McGuire’s Utterances in the Novel Savage Land - Astuti, Retno Budi (CV. Mitra Palupi, 2021)
Background: Â Politeness is a common strategy that is used by most of speakers; even the English native speakers do such thing to their counterparts as well. It is especially appropriate when someone is making a request, talking on the telephone or engaging in a pleasant conversation with someone else. However, there are different opinions about what is and is not considered as polite since there are distinctions in culture from one country to other countries all over the world.Purpose: research aims to find out the negative politeness strategies which is used by Colleen McGuire in her utterances as the main character of the novel Savage Land.Design and methods: This research use a qualitative method. The data source that is used in this research is taken from the dialogues uttered by Colleen McGuire as the main female character in the novel Savage Land.Results: From the 10 strategies of negative politeness strategy according to Brown Levinsonâ€™s theory, the writer found the total of 4 strategies which was used by the main female character, Colleen McGuire, in the novel Savage Land. Those 4 strategies are hedge, be pessimistic, minimize the imposition, and impersonalize the speaker to the addressee.